EC 202 - Introduction to Macroeconomics - Linn Benton Virtual College (2018)
This course introduces the determination of levels of national income, employment and prices, and the basic causes of fluctuations in the business cycle, the banking system, monetary policy and financial intermediation. Other topics may include international trade and international finance.